Effect of blade inclination angle for straight-bladed vertical-axis wind turbines - L. Morgan; A. K. Amiri; W. Leithead; J. Carroll (Wind Energy Science)
Vertical-axis wind turbines (VAWTs) have received renewed research interest in the offshore environment due to a number of design synergies that have the potential to decrease the cost of energy for offshore wind. Many studies have been completed on the rotor design for straight-bladed rotors (H-rotors); however, there is sparse information on the effect of blade inclination angle on VAWT aerodynamic performance and the optimal blade design of VAWTs with inclined blades (V-rotors) for maximum power capture.